Alleviating heat stress effects in poultry: updates on methods and mechanisms of actions - Onagbesan, Okanlawon M.; Uyanga, Victoria Anthony; Oso, Oluwadamilola; Tona, Kokou; Oke, Oyegunle Emmanuel (Frontiers in Veterinary Science, 2023)
Heat stress is a threat to the environment that can lead to significant financial losses in the production of poultry in the world's tropical and arid regions. The degree of heat stress (mild, moderate, severe) experienced by poultry depends mainly on humidity, thermal irradiation, humidity, the animal's thermoregulatory ability, metabolic rate, age, intensity, and duration of the heat stress. Contemporary commercial broiler chickens have a rapid metabolism, which makes them produce higher heat and be prone to heat stress. The negative effect of heat stress on poultry birds' physiology, health, production, welfare, and behaviours are reviewed in detail in this manuscriptwork. The appropriate mitigation strategies highlighted in the literature for heat stress in poultry are equally explored in this review. Interestingly, each of these strategies finds its application applicability at different stages of a poultry's lifecycle. For instance, gene mapping prior to breeding and genetic selection during breeding are promising tools for developing heatresistant breeds. Thermal conditioning during embryonic development or early life enhances the ability of birds to tolerate heat during their adult life. Nutritional management such as dietary manipulations, nighttime feeding, and wet feeding often applied with timely and effective correction of environmental conditions have been proven to ameliorate the effect of heat stress in chicks and adult birds. As long as the climatic crises persist, heat stress may continue to require considerable attention, thus it is imperative to explore the current happenings and pay attention to the future trajectory ends of heat stress effects on poultry productionthis.